Changes in Suicide Rate and Characteristics According to Age of Suicide Attempters before and after COVID-19 - Min-Jung Kim; So-Hyun Paek; Jae-Hyun Kwon; Soo-Hyun Park; Hyun-Jung Chung; Young-Hoon Byun (MDPI AG, 2022)
This study aims to identify age-related suicide-related factors and changes in suicide rate before and after the onset of the COVID-19 pandemic. Methods: From 2018 to 2020, the patients who presented to the ED of a university hospital with a suicide attempt were classified into adolescents (≤18 years), adults (19-65 years), and elderly (>65 years), and the visits were grouped into before and after COVID-19. Results: There were 853 visits before and 388 visits after COVID-19, and the results showed that the number of adolescent and adult suicide patients increased immediately after the pandemic, but the overall trend did not show a significant difference from before the pandemic. In the adolescents, the ratio of male patients increased, interpersonal and school-related motivations decreased, the poisoning and cutting methods of suicide were more common, and hospitalization admissions increased. Among the elderly, the ratio of female patients increased, the number of single patients and patients without previous psychiatric problems increased, the motives for physical illness and death of people around increased, the falling and hanging methods of suicide were more common, and hospitalization admissions and deaths increased. Conclusion: The impact of COVID-19 on suicide rates and suicide-related factors varies by age group. This finding requires different approaches and methods to suicide prevention based on age.